Mapes of secondary sources in the problem of ERT probing 2D medium: numerical method and analytical solutions - Rakisheva, D.S.; Modin, I.N.; Mukanova, B.G. (KSU Publ., 2020)
The paper considers a mathematical model of electrical tomography above the media with local inclusions. Numerical solutions of a system of integral equations for a medium with local inclusion are compared against a numerical implementation of the analytical solution of the problem for a case of a sphere in homogeneous space. The parameters of local inclusion and the depth of heterogeneity are varied. Maps of secondary sources in the ERT (Electrical Resistivity Tomography) probing problem are constructed: for local inclusion in the form of the ellipsoid, an ellipsoid in a homogeneous space (analytical solution of the problem) and for two-layer half-spaces as well. Numerical results are presented, and maps of secondary sources in the cases where the immersed heterogeneity is an insulator and a conductor are computed.
2D орталарының ERT зондтау есебіндегі қайталама зарядтардың карталары: сандық әдіс және аналитикалық шешімдер
Карты вторичных источников в задаче ERT зондирования 2D сред: численный метод и аналитические решения
Keywords: map of secondary sources; analytical solution of the problem with immersed heterogeneity; ellipsoid in a homogeneous space; the integral equation method